PENAKSIRAN KESENJANGAN OUTPUT INDONESIA: APLIKASI METODE KALMAN FILTER DAN HODRICK-PRESCOTT FILTER - Priyono, Teguh Hadi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2008)
This research will measure the potential output in Indonesia using Kalman-filterand Hodrick-Prescott Filter. The model will observe the variations of output gapand inflation in Indonesia. The model of Kalman Filter shows a long-term trend ofoutput nearly to actual output than the other model, however it shows a slow responsethan Hodrick-Prescott Filter.Keywords: Output Gap, Inflation, Kalman filter and Hodrick – Prescote Filter.